2005
DOI: 10.1002/adfm.200400220
|View full text |Cite
|
Sign up to set email alerts
|

Titania and Mixed Titania/Aluminum, Gallium, or Indium Oxide Spheres: Sol–Gel/Template Synthesis and Photocatalytic Properties

Abstract: Porous polymer beads have been used as templates in which sol–gel chemistry was conducted for the formation of porous titanium dioxide and titania/aluminum, gallium, or indium oxide spheres. The addition of 5, 10, and 15 wt.‐% of the second metal oxide to titania was studied, resulting in little variation in the final porous‐sphere diameter, but in a decreased titania nanocrystal size and an increased specific surface area of the material. The crystallinity of the samples was observed after heating at 550, 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 49 publications
(46 reference statements)
1
66
0
Order By: Relevance
“…The pH of the 2-chlorophenol solution also influences the photocatalytic efficiency of the materials and is currently being investigated for materials obtained using templating techniques. [20] It has been shown that the addition of a small amount of non-photoactive metal oxide can increase the photocatalytic efficiency of titania due to its influence on a number of the materials' properties, including the adsorption behavior and surface acidity of the composite. [21,22] As discussed previously, the addition of the second metal oxide also increased the specific surface area of the metal oxide film and stabilized the more photocatalytically active anatase phase of titania.…”
Section: Photocatalysismentioning
confidence: 99%
“…The pH of the 2-chlorophenol solution also influences the photocatalytic efficiency of the materials and is currently being investigated for materials obtained using templating techniques. [20] It has been shown that the addition of a small amount of non-photoactive metal oxide can increase the photocatalytic efficiency of titania due to its influence on a number of the materials' properties, including the adsorption behavior and surface acidity of the composite. [21,22] As discussed previously, the addition of the second metal oxide also increased the specific surface area of the metal oxide film and stabilized the more photocatalytically active anatase phase of titania.…”
Section: Photocatalysismentioning
confidence: 99%
“…It is well known that the presence of templates such as surfactants in sol-gel chemistry plays a crucial role in creating the porous structure of the TiO 2 inorganic network, which reduces the hydraulic resistance of TiO 2 membranes and enhances their photocatalytic activity. [20][21][22][23] In this method, the surfactant concentration largely affects the structural properties of the TiO 2 material. [24,25] Controlling materials at the nanoscale makes it possible to develop new types of catalytic membrane products with tailor-designed properties exhibiting a hierarchical change in the diameter of the mesopore from the top to the bottom of the TiO 2 skin layer.…”
Section: Introductionmentioning
confidence: 99%
“…During a heating step in which the titania is crystallized, the organic material is removed through pyrolysis, thus leaving a titania network with a structure reminiscent of the initial template. Spherical templates that have been applied to the synthesis of titania spheres include porous beads of polystyrene crosslinked with divinyl benzene, [62][63][64] mesoporous carbon spheres formed themselves through a templating process involving mesoporous silica spheres, [ 65 ] and spherical macroporous biopolymer gels (e.g., agarose and alginate). [66][67][68] Prof. Rachel A.…”
Section: Templating Methods Using Preformed Hard Templatesmentioning
confidence: 99%
“…[ 74 ] Yang and co-workers found that the diameter of the titania microspheres ( d m ) can be removing micrometer diameter beads over nanoparticles has to be considered. [ 64 ] Hydroxyl functionalized polystyrene crosslinked with divinyl benzene beads having a diameter of 11.5 μ m were used for infi ltration with preformed titania nanoparticles (4 nm in diameter). [ 63 ] The fi nal diameter of the titania beads produced was 5 μ m, and the beads were composed of both the anatase and rutile phase with a surface area of 81 m 2 g − 1 .…”
Section: Emulsion-mediated Synthesismentioning
confidence: 99%